1985
DOI: 10.1128/jb.162.2.543-550.1985
|View full text |Cite
|
Sign up to set email alerts
|

Mating system for transfer of plasmids among Bacillus anthracis, Bacillus cereus, and Bacillus thuringiensis

Abstract: To facilitate the analysis of genetic determinants carried by large resident plasmids of Bacillus anthracis, a mating system was developed which promotes plasmid transfer among strains of B. anthracis, B. cereus, and B. thuringiensis. Transfer of the selectable tetracycline resistance plasmid pBC16 and other plasmids from B. thuringiensis to B. anthracis and B. cereus recipients occurred during mixed incubation in broth. Two plasmids, pXOll and pXO12, found in B. thuringiensis were responsible for plasmid mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(36 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…The B. cereus large plasmids harbor candidate pore formation genes, such as the TraD/G conjugation proteins, that could form a pore through a membrane complex however their functionality has not been demonstrated experimentally. Sequencing of mobilizable B. cereus group plasmids such as pOX11 [92], pXO12 [92] or pXO16 [74,104] would advance our understanding of plasmid transfer mechanisms in this group of organisms. A number of limited studies have been undertaken that demonstrate that B. cereus group plasmid transfer is not affected by DNase, involves membrane interaction [74] and in some cases employs an Ôaggregation sub-stanceÕ [104], all which suggest a conjugative transfer mechanism.…”
Section: Plasmid Mobilitymentioning
confidence: 99%
“…The B. cereus large plasmids harbor candidate pore formation genes, such as the TraD/G conjugation proteins, that could form a pore through a membrane complex however their functionality has not been demonstrated experimentally. Sequencing of mobilizable B. cereus group plasmids such as pOX11 [92], pXO12 [92] or pXO16 [74,104] would advance our understanding of plasmid transfer mechanisms in this group of organisms. A number of limited studies have been undertaken that demonstrate that B. cereus group plasmid transfer is not affected by DNase, involves membrane interaction [74] and in some cases employs an Ôaggregation sub-stanceÕ [104], all which suggest a conjugative transfer mechanism.…”
Section: Plasmid Mobilitymentioning
confidence: 99%
“…2B). Transfer of B. thuringiensis plasmids encoding Cry proteins has been described [12,13], but to our knowledge this is the ¢rst description of B. thuringiensis plasmid transfer to B. mycoides. Although several attempts were made, we were unable to transfer the pHT73-Em R to B. weihenstephanensis and to ¢ve B. cereus strains among which one was an emetic isolate.…”
Section: Recipient Host Range Of Pht73-em Rmentioning
confidence: 99%
“…israelensis pXO16 plasmid. Battisti et al [13] observed a limited host range among donors in conjugation experiments, as only 83% of B. thuringiensis strains containing pBC16 were able to transfer this plasmid to a B. cereus strain, and only 50% of the B. thuringiensis strains were able to transfer pBC16 to a B. anthracis strain.…”
Section: Recipient Host Range Of Pht73-em Rmentioning
confidence: 99%
“…Bacillus anthracis, the agent of anthrax, causes a highly infectious disease in domestic animals and humans. The two major virulence factors of B. anthracis are a poly-D-glutamic acid capsule and a tripartite toxin, which are associated with large plasmids, 60 and 110 MDa plasmid, respectively [1][2][3]. Recently, one of these toxin genes was cloned in Escherichia coli [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…anthracis were not examined at all, because of the lack of a suitable method for phenotypic expression in B. anthracis. The introduction of plasmid DNA into B. anthracis has been achieved by transduction [6] and mobilization [1]. These are rather laborious methods and not widely applicable in recombinant DNA technology.…”
Section: Introductionmentioning
confidence: 99%